The Effect of Principal Academic Supervision, Teacher Competence, and Work Environment on Elementary School Teacher Productivity - Shintawati, Shintawati; Hanafi, Muhammad Syadeli; Hendrayana, Aan (Jurnal Pendidikan Indonesia Gemilang, 2025)
This study focused on teacher productivity in Tangerang city public primary schools. Teachers face challenges such as administrative duties and changing curriculum. The research aimed to examine how principal supervision, teacher competence, and work environment affect elementary school teacher productivity in Tangerang city, Indonesia. The study used a quantitative descriptive literature review method. It analyzes 28 scientific articles. The results show that teacher competence has the highest impact on productivity. Academic supervision also influences productivity significantly. The work environment has a lesser, but important, effect. Managing these factors together can improve teacher performance. The study suggests continuous professional development is needed. Principals should provide supportive supervision. A positive work environment helps maintain motivation. The findings guide teachers and principals in Tangerang. They also help education policymakers. The goal is to improve teacher productivity and student outcomes. These recommendations aim for sustainable education improvements.